52 square meters
15 square meters
104 square meters
diagram below.
what is the solution to the system of equations
2x + 6y = -6 ...(1)
4x - 3y = -12 ...(2)
We can use the method of substitution or elimination to find the solution. I will use the method of substitution.
From equation (1), we can solve for x in terms of y:
2x = -6 - 6y
x = (-6 - 6y)/2
x = -3 - 3y
Now, substitute this value of x into equation (2):
4(-3 - 3y) - 3y = -12
-12 - 12y - 3y = -12
-15y = 0
y = 0
Substitute this value of y back into equation (1) to find x:
2x + 6(0) = -6
2x = -6
x = -3
Therefore, the solution to the system of equations is x = -3 and y = 0.
hope this helps
Answer:
x = -3, y = 0
Step-by-step explanation:
2x+6y=-6 equation1
4x-3y=-12 equation2
multiply equation2 by 2
2[ 4x-3y=-12]
8x - 6y = -24 equation3
add equations 1 & 3
2x+6y=-6
8x - 6y = -24
--------------------
10x = -30
x = -3
substitute x = -3 to any of the equations
I will use equation1
2x+6y=-6
2(-3) + 6y = -6
-6 + 6y = -6
6y = 0
y = 0
$0.45
$1.55
$2.05
1/x+1; where x ≠ -1, -5
1/x-5; where x ≠ 5
x-5
Answer:
The correct option is 2.
Step-by-step explanation:
The given rational expression is
Factorize the denominator.
The middle term can be written as 5x+x.
Cancel out the common factors.
The simplified form of the given expression is . The factors of the denominator are (x+5) and (x+1), it means at x=-5 and x=-1, the value of denominator is zero.
The given expression is not defined for x=-1 and x=-5.
Therefore the correct option is 2.